Sustainability Model from Cradle-to-Gate: Residential Buildings in Palestine - Abu Hanieh, Ahmed; Karaeen, Mohammad; Hasan, Afif Akel (International Journal of Sustainable Construction Engineering and Technology, 2022)
Aim of study is to develop a sustainable model for residential building sector in Palestine by tracking the sector from cradle to end of construction process. In the sustainability model, all input resources to the model will be specified and connect to the outputs of the building process involving all dynamic contributors; labor, water, and energy. Based on the sustainability supply chain a model is implemented for a 100 m2 residential building. For the implemented case study all, necessary costs have been included showing the total cost of this building. The Value Creation Index of the investigated case has been estimated showing the ratio between the revenues gained by the local contracting companies and cost incurred in the building. The large consumed resources indicate the importance and need for creating a sustainability model for the sector.